Correlations between dissociation, absorption and fantasy proneness with hallucinatory experiences in healthy population - Parra, Alejandro (2007)
The continuum hypothesis of psychosis suggests that symptoms as well as hallucinations can make part of normal consciousness in the general population. In the present study we examined three factors hypothetically related to hallucinatory experiences: fantasy proneness, psychological absorption and dissociative experiences. We surveyed a sample of 650 university students of both sexes (24% males and 76% females; ages 17-57 years) and found significant differences in absorption (r= .61 p < .001) and –although somewhat less– fantasy proneness (r= .54; p < .001) and dissociation (r= .55; p < .001) with the total hallucination score. Given the consistency of our findings with regard to absorption, dissociation, and fantasy proneness, we conclude a validation of hallucinatory experiences in the normal population.